Growth factor concentrations in platelet‐rich plasma for androgenetic alopecia: An intra‐subject, randomized, blinded, placebo‐controlled, pilot study - Siah, Tee Wei; Guo, Hongwei; Chu, Thomas; Santos, Leopoldo; Nakamura, Hisae; Leung, Gigi; Shapiro, Jerry; McElwee, Kevin J. (Experimental dermatology, 2020)
Background Platelet‐rich plasma (PRP), processed from autologous peripheral blood, is used to treat androgenetic alopecia (AGA). Objective To determine the efficacy of PRP for hair growth promotion in AGA patients in a randomized, blinded, placebo‐controlled, pilot clinical trial (NCT02074943). Methods The efficacy of an 8 week, five session, PRP treatment course was determined by measuring hair density and hair caliber changes in 10 AGA affected patients. For each PRP sample, the concentrations of selected growth factors were determined using a multiplex assay system. The clinical results were then correlated with the growth factor concentrations in PRP. Results At 16 weeks, 8 weeks after the last PRP injection, treated areas exhibited increased mean hair density (+12.76%) over baseline compared to placebo (+0.99%). Mean hair caliber decreased in both treated and placebo regions (−16.22% and −19.46%, respectively). Serial analysis of PRP significant variability in concentrations between patients. Overall, there was a positive correlation between GDNF concentration and hair density (P = .004). Trends, though not statistically significant, were also observed for FGF2 and VEGF. Limitations Small sample size and lack of comparative cohorts receiving protocol variations limit confidence in the study data. Conclusions This small pilot clinical trial suggests PRP treatment may be beneficial for AGA. However, the variable hair growth responses between patients indicate there is a significant opportunity to improve PRP therapy protocols for hair growth promotion. The variability in growth factor concentration in PRP suggests standardization of growth factors postprocessing might improve hair growth responses.